(untitled) (Research, Society and Development, 2022)
Objective: The goals for this study were to present the history of the CAD/CAM system and the advantages of this system and other technological innovations in the clinician’s daily dental practice. In addition to presenting a case report of a patient’s treatment performed through DSD planning. Methodology: The entire aesthetic planning was demonstrated using the DSD and the patient additive mockup technique. After obtaining the 3D model, digital aesthetic planning was performed. In the manufacture of ceramic veneers, the CAD/CAM system was used. Then, the gingival removal and subsequent intra-oral scanning of the prepared region were performed. Photo-activatable adhesive cementation was used in the placement of the ceramic veneers, in addition to receiving a surface treatment, followed by the application of the adhesive system. Results: The result met the expectations of the patient, who was able to visualize the forecast of the final result. Conclusion: It was concluded that, although the CAD/CAM system has advantages, it is necessary for the professional’s higher learning curve, with both techniques, both digital and analog, being adequate and efficient.